Empatia médica e o sofrimento mental: uma abordagem na atenção básica - Luchini Junior, Deoclécio (2019)
The approach to mental suffering by Primary Care doctors is one of the main axis emphasized in the National Primary Care Policy, requiring a range of abilities from the professional that works with it. The relevance of empathy in the process of developing the doctor-patient relationship and all the products arising from this interaction stands out. As a means to analyze the possible consequences that an empathic relationship brings to the rendering of care, a research that identified the aspects related to empathy in doctors acting in Primary Care during the attendance of a person with mental suffering was developed. The methodology was qualitative, athwart exploring semistructured interviews developed with generalist doctors working in Primary Care in four health centers, the two with the largest and the two with the smallest psychotropic dispensation rates. Based upon the data, three analytical categories arose: empathy identified in the doctor’s active listening, strategies that allow better service to the patient and mobilization of feelings. It was observed that, despite inherent to the doctor-patient relationship, empathy wasn’t a constant; however, its perceived that the greater mobilization of it and the more appropriate its use, more resolutive the medical consult becomes. That was demonstrated to be particularly important in mental health accessing appointments for subserving the doctor and patient interaction and providing solace for the last one to share their anguishes, creating bonds and participating in the process of the therapeutic contract. In this manner, it’s possible to conclude empathy as a technical ability with extended scientific advocacy in its utilization and that it provides positive results, being a primordial tool in the attendance of a person that suffers.